(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2015)
Tuberculosis (TB) is a chronic granulomatous disease and a leading cause of death in developing countries. Mucous membrane (oral/genital/perianal) TB could be either primary or secondary to autoinoculation of Mycobacterium tuberculosis from underlying advanced TB infection of lung, genitourinary or gastrointestinal tract respectively. Involvement of oral cavity in TB is quite rare, so difficult to get diagnosed. Hence we are reporting a case of TB of oral (buccal) mucosa in a 22 year old male who presented with painful ulcerative growth on left side of buccal mucosa near the molar teeth since 5 months. Diagnosis was made on histopathological examination and Ziehl Neelsen (ZN) staining of biopsy specimen. The complete blood count, chest X-ray, culture of tissue biopsy and sputum showed findings consistent with Mycobacterium tuberculosis infection. Patient responded to the treatment with complete recovery of tuberculosis oral lesion. Hence awareness of rare form of oral tuberculosis makes early diagnosis and prevents further spread of disease. DOI: http://dx.doi.org/10.3126/saarctb.v11i2.12438 SAARC J TUBER LUNG DIS HIV/AIDS, 2014;XI(2) Page: 37-39